Determination of lactic acid produced by fermentation of some sugars by streptococcus mutans and streptococcus sanguis - Jintakorn Kuvatanasuchati (Chulalongkorn University, 2014)
Thesis (M.Sc. in Pharm)--Chulalongkorn University, 1981